IMPLEMENTASI PEMENUHAN HAK MENDAPATKAN MAKANAN YANG LAYAK BAGI NARAPIDANA DI LEMBAGA PEMASYARAKATAN KLAS 1 MAKASSAR - Manan Sailan; Irfana Lutia Ilyas (Universitas Negeri Makassar, 2018)
This study aims to determine the fulfillment of the implementation of the right to get a decent meal for inmates in prisons Class I Makassar, obstacles faced in the implementation of the correctional institution fulfilling the right to get a decent meal for inmates at the Correctional Institution Class I Makassar. To achieve these objectives, the technique of collecting data through observation, interviews, and documentation. Data obtained from the research that was processed using descriptive and qualitative analysis to determine compliance with the implementation of the right to adequate food in prisonsJurnal Supremasi ISSN 1412-517X95Class I Makassar. The results showed that: 1. Implementation of the fulfillment of the right to adequate food for prisoners in institutions pemasyaraktan class 1 Makassar has not been feasible. Prisoners often complain the food they consume less palatable to various reasons including less attention to food hygiene, flavors that are less and less balanced nutritional meal. Later in the implementation process of the fulfillment of the right to get a decent meal for inmates there are some things that are not in accordance with the procedures of the Decree of the Minister of Law and Human Rights No. M.HH-01.PK.07.02 Year 2009 on Guidelines for the Implementation of Food for People in Prison Correctional Patronage and the State Prison (Rutan). So that the implementation of the fulfillment of the right to get a decent meal for inmates under Act No. 12 of 1995 concerning Corrections has not done well. 2. Constraints faced by not performing well fulfillment of the right to get a decent meal for inmates Penitentiary Class 1 Makassar such a low budget so the impact on infrastructure facilities and inadequate infrastructure. Unavailability cook expert in Penitentiary and nutritionists to assess directly the served meals nutritious or not, so the impact on the poor quality of food and nutrition unbalanced diet. Then the capacity of prisons is not balanced by the number of prisoners is increasing (over capacity), which resulted in the implementation of the fulfillment of the right to get a decent meal is not maximized.